The Jewish Reception of Aristotle’s Poetics in Thirteenth- and Fourteenth-century Provence: A Survey of the Arabic Sources - Gorgoni, Francesca (European journal of jewish studies, 2022)
The last few years have seen a renewed interest in Aristotle’s logic in the Jewish tradition, giving a decisive impulse to the research on the Greek-into-Hebrew philosophical transmission in medieval and early modern times. The present article aims to contribute to the studies on Aristotelian logic in Hebrew by focusing on a less explored aspect, namely the reception of Aristotle’s Poetics in Jewish culture.